Portuguese Foundation Graphogame: preliminary results - Sucena, Ana (2019)
he Portuguese Foundation Graphogame is an adaptation of the Graphogame software to European Portuguese. The Graphogame contributes to reading and spelling acquisition. It has been designed and implemented for different languages with results that reveal that this is an effective tool to the reading and spelling acquisition. In this paper the methodology adopted in Portuguese Graphogame and the results of its implementation in schools are described.